2014
DOI: 10.1074/jbc.m114.559187
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CD44-binding Peptide from the Pro-Matrix Metalloproteinase-9 Hemopexin Domain Impairs Adhesion and Migration of Chronic Lymphocytic Leukemia (CLL) Cells

Abstract: Background: proMMP-9 binds to CLL cells through the hemopexin domain (PEX9), contributing to disease progression. Results: A 20-residue sequence (P6) within PEX9 inhibits CD44-mediated CLL-proMMP-9 interaction and cell migration. P6 cooperates with the previously identified sequence P3, also located in PEX9. Conclusion: P6 is a CD44-binding site and impairs proMMP-9 effects on CLL. Significance: P6 may be a novel therapeutic target in CLL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Sequence-alignment studies of human MMP9 revealed that its PEX9 domain shows low homology with other MMP PEX domains (25%-30% amino acid identity), thereby suggesting PEX9 as a potential therapeutic target for selective MMP9 inhibition. 114,115 Ugarte-Berzal et al also have shown that although MMP9 degrades gelatin, the PEX9 domain inhibits this degradation by shielding gelatin and averting its interaction with the MMP9 catalytic site. 114,115 The PEX9 domain may regulate intracellular signaling and survival in chronic lymphocytic leukemia (CLL) cells.…”
Section: Mmps As Signaling Molecules Noncatalytic Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sequence-alignment studies of human MMP9 revealed that its PEX9 domain shows low homology with other MMP PEX domains (25%-30% amino acid identity), thereby suggesting PEX9 as a potential therapeutic target for selective MMP9 inhibition. 114,115 Ugarte-Berzal et al also have shown that although MMP9 degrades gelatin, the PEX9 domain inhibits this degradation by shielding gelatin and averting its interaction with the MMP9 catalytic site. 114,115 The PEX9 domain may regulate intracellular signaling and survival in chronic lymphocytic leukemia (CLL) cells.…”
Section: Mmps As Signaling Molecules Noncatalytic Functionsmentioning
confidence: 99%
“…114,115 Ugarte-Berzal et al also have shown that although MMP9 degrades gelatin, the PEX9 domain inhibits this degradation by shielding gelatin and averting its interaction with the MMP9 catalytic site. 114,115 The PEX9 domain may regulate intracellular signaling and survival in chronic lymphocytic leukemia (CLL) cells. 114,115 Ugarte-Berzal et al reported that the PEX9 domain contributes to CLL progression, and found a connection between blade B4 and the α 4 β 1 integrin.…”
Section: Mmps As Signaling Molecules Noncatalytic Functionsmentioning
confidence: 99%
See 3 more Smart Citations